ЭКОИННОВАЦИИ В ТРАНСПОРТЕ И ЭНЕРГЕТИКЕ КАК СПОСОБ РЕШЕНИЯ ПРОБЛЕМЫ ИЗМЕНЕНИЯ КЛИМАТА (World Science, 2019)
The analysis of the market of electric transport and renewable energy in the world and the impact of the development of these industries on export diversification and economic growth of countries was carried out. The impact of eco-innovation on world markets and international trade has been determined, experience in supporting eco-innovation industries has been systematized, and the impact of this support on economic growth and diversification of countries' exports has been studied. It has been revealed that the development of electric transport takes place on the basis of the existing automotive industry, however, for countries with small economies, especially exporters of raw materials, it becomes economically feasible to support electrification of all vehicles within the country and the development of alternative energy sources to reduce the load on the environment due to the increasing load on the grid.